2003
DOI: 10.1136/jmg.40.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CD14 gene -159C polymorphism with progression of IgA nephropathy

Abstract: The risk factors associated with the progression of IgA nephropathy (IgAN), the most common form of glomerulonephritis, are unclear. It has been suggested that CD14 signalling in response to various microbes affects the natural history of chronic inflammatory conditions. It has been hypothesised that variants in the promoter region of the CD14 gene might alter the expression of CD14, and this in turn could influence the progressive nature of IgAN. PCR-RFLP was used to determine the polymorphism at the −159 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 30 publications
(17 reference statements)
0
26
1
1
Order By: Relevance
“…Recently, a significant correlation was shown between expression of TLR4 on circulating mononuclear cells (CD14-positive cells) and amount of proteinuria in patients with IgAN [7]. In a previous study, the association of CD14 gene-159C polymorphism with progression of IgAN was also reported [23]. Based on these findings, Coppo et al suggested that TLR4 engagement in circulating mononuclear cells could play a role in the development of glomerular inflammation and a possible specific involvement in active and progressive IgAN [7].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a significant correlation was shown between expression of TLR4 on circulating mononuclear cells (CD14-positive cells) and amount of proteinuria in patients with IgAN [7]. In a previous study, the association of CD14 gene-159C polymorphism with progression of IgAN was also reported [23]. Based on these findings, Coppo et al suggested that TLR4 engagement in circulating mononuclear cells could play a role in the development of glomerular inflammation and a possible specific involvement in active and progressive IgAN [7].…”
Section: Discussionmentioning
confidence: 94%
“…When there is familial predisposition to the disease [9], the prognosis is less favorable, especially in kidney transplantation recipients [5]. Other predisposing factors include linkages to 6q22-23 and CD14/-159 polymorphism [10,11,12]. Finally, downregulation of podocyte nephrin may contribute to the development or progression of IgA nephropathy [13].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Haraka et al [19] demonstrated a worsening prognosis if urinary IL-6 excretion exceeds 2.5 ng/day. Yoon et al [10] evaluated the association of CD14-159C polymorphism with a deteriorating prognosis. Florquin et al [20] demonstrated that CD44 expression was associated with poor prognosis.…”
Section: Histopathologic Features and Other Markers Of Progressionmentioning
confidence: 99%
“…[2,10] Although the present study showed that CD14 -159T allele was associated with decreased kidney function, and that most previous studies also found that subjects with T allele or TT genotype have a higher risk of atherosclerotic diseases, other studies have reported the controversial finding that CC genotype was associated with atherosclerotic diseases. [13][14][15] One study [13] reported that CD14 -159CC genotype was associated with increased carotid atherosclerosis only in smokers. However, this result might be modified by smoking, as a significant interaction was observed between smoking and CD14 genotype in sCD14 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis patients, however, who are exposed to higher levels of endotoxin, might be CD14 C-159T Polymorphism and Decreased GFR 971 influenced by CD14 polymorphism in a different or even an opposite way. [17] Although among patients with IgA nephropathy, [15] CC genotype was associated with the progression of renal insufficiency, it is known to be associated with higher levels of IgE and allergic diseases, [3] and IgE may play a role in the pathogenesis of IgA nephropathy. [18] These contradictory findings could in part be explained by differences in the ethnic backgrounds of the study populations or by random variations due to subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%